Solid Lipid Nanoparticles Enhancing the Leishmanicidal Activity of Delamanid - Santamaría-Aguirre, Javier; Jacho, Daniela; Méndez, Miguel A.; Poveda, Ana; Carrión, Javier; Fanarraga, Mónica L. (Pharmaceutics, 2023)
Leishmaniasis, a zoonotic parasitic disease transmitted by infected sandflies, impacts nearly 1 million people yearly and is endemic in many countries across Asia, Africa, the Americas, and the Mediterranean; despite this, it remains a neglected disease with limited effective treatments, particularly in impoverished communities with limited access to healthcare. This study aims to repurpose approved drugs for an affordable leishmaniasis treatment. After the screening of potential drug candidates by reviewing databases and utilizing molecular docking analysis, delamanid was chosen to be incorporated into solid lipid nanoparticles (SLNPs). Both in cellulo and in vivo tests confirmed the successful payload release within macrophages and through the epidermis following topical application on murine skin. The evaluation of macrophages infected with L. infantum amastigotes showed that the encapsulated delamanid exhibited greater leishmanicidal activity compared with the free drug. The process of encapsulating delamanid in SLNPs, as demonstrated in this study, places a strong emphasis on employing minimal technology, ensuring energy efficiency, cost-effectiveness, and reproducibility. It enables consistent, low-cost production of nanomedicines, even on a small scale, offering a promising step toward more accessible and effective leishmaniasis treatments.